The Relationship Between Diet and Physical Activity with Uric Acid Levels in the Elderly in the Working Area of the Padasuka Central Cimahi Health Center - Rudyana, Hikmat; Yuswandi, Yuswandi; Rosila, Anggi Dara; Santoso, Budi; Akbar, Teguh; Supriadi, Dedi; Saadah, Hindun (Sean Institute, 2023)
This study aims to determine the relationship between diet and physical activity with uric acid levels in the elderly in the Padasuka Health Center Working Area. Cross sectional research design. A sample of 78 respondents was taken with the Stratified Random Sampling Technique. Primary data collection was obtained through interviews and checking the community in RW 14. Based on Univariate Results most respondents with high purine consumption patterns were 40 people (51.3%). Most respondents with moderate physical activity were 28 people (35.9%). Then most of the respondents with abnormal uric acid levels were 48 people (61.5%). Bivariate results showed no relationship between diet and uric acid levels in the elderly in RW 14 Padasuka Village, Padasuka Health Center Working Area (p = 0.070). There is no relationship between physical activity and uric acid levels in the elderly in RW 14 Padasuka Village, Padasuka Health Center Working Area (p = 0.819). There is no relationship between diet and physical activity with uric acid levels in the elderly in RW 14 Padasuka Village. It is expected for the RW 14 community to better maintain their diet and lifestyle so that uric acid levels are not high.